KAJIAN POTENSI DAN STRATEGI KEBIJAKAN PENGEMBANGAN PARIWISATA KAWASAN WISATA PULAU JACO DISTRIC LOSPALOS TIMOR LESTE - , Amancio Marques ([Yogyakarta] : Universitas Gadjah Mada, 2011)
AMANCIO MARQUES, Study of Potency and Tourism Developing Strategy of Jaco Island in Distric Lospalos Timor Leste. Master Program of Gadjah Mada University of Public Policy, Yogyakarta. The problrm which can be met in the managing potency of Javo Island were the existing potency of Jaco Island not been managed as professionally. Among creating new opportunities to tourism product can be exeeded. Design of research used is descriptive research both qualitative abd quantitative. Technique of data collecting conducted through direct survey, observe, questioner and deep interview with informan who related with this research and specified by purposive sampling. While data analysis in this research is conducted by SWOT analysis includeing Strengths, Weakness, Opportunity, and Threats. Result of research identify that exixting potency in Lospalos very large, however not entirely managed as professionally, because pursued some problems such as support of fund and personal capability still were limited. Development strategy which can be conducted by management of Jaco Island were improve governmental commitment in manage Jaco Island. Governmental policy that is by specifying some model of product developing tourism object in covering conventional tourism, ecotourism, agricultur tourism, and ethnic tourism, even if government able to integrate some model of them through planning of tourism development based on empowerment of society and optimal marketing activity so that able to draw the touris. Govermental policy in reaching opportunity and answer to the internal problems conducted through basic of ability in tourism knowledge and english as second language for local society. Government and entire stakeholder to improve the human resource quality and developing of accomodation and its facilities.